In and out of the niche: perspectives in mobilization of hematopoietic stem cells - Mohty, Mohamad; Ho, Anthony Dick (Experimental hematology, 2011)
Several stem cell mobilization strategies have been employed in the past 2 decades, including chemotherapy, hematopoietic growth factors, and chemotherapy plus growth factors. Granulocyte colony-stimulating factor (G-CSF) and granulocyte-macrophage CSF are standard agents approved for peripheral blood stem cell mobilization since the early 1990s. Between 5% and 20% of patients, however, fail to mobilize a sufficient numbers of peripheral blood stem cells in response to G-CSF with or without chemotherapy. Recent advances in defining the basic mechanisms regulating the interactions between hematopoietic stem cells and their marrow niche had led to the discovery that CXCR4 and stromal-cell−derived factor 1α axis play a significant role. Plerixafor, an antagonist of the CXCR4-stromal-cell−derived factor 1α axis has been shown to result in a significant mobilization of hematopoietic stem cells. Numerous clinical trials have demonstrated that the combination of G-CSF and AMD3100 (G+A) resulted in a significant increase in CD34+ cell yield as compared to the administration of G-CSF alone. In particular, the progenitors mobilized have been shown to comprise a significantly higher proportion of primitive and possibly more potent CD34+/CD38- subpopulation. Transplantation of PBSC mobilized by G+A administration have led to a rapid and sustained neutrophil and platelet engraftment. Another prospective role of this new class of agents might lie in the mobilization of dormant leukemia stem cells that are well protected by the niche. The future role of CXCR4 antagonists in treatment of hematologic malignancies includes mobilization of hematopoietic stem cells for transplantation and mobilization of leukemia-initiating cells for long-term cure.
Gesehen am 01.09.2022